Risk analysis for confined space entries: Critical analysis of four tools applied to three risk scenarios. Issue 6 (2nd June 2016) - Burlet-Vienney, Damien; Chinniah, Yuvin; Bahloul, Ali; Roberge, Brigitte
ABSTRACT: Investigation reports of fatal confined space accidents nearly always point to a problem of identifying or underestimating risks. This paper compares 4 different risk analysis tools developed for confined spaces by applying them to 3 hazardous scenarios. The tools were namely 1. a checklist without risk estimation (Tool A), 2. a checklist with a risk scale (Tool B), 3. a risk calculation without a formal hazard identification stage (Tool C), and 4. a questionnaire followed by a risk matrix (Tool D). Each tool's structure and practical application were studied. Tools A and B gave crude results comparable to those of more analytic tools in less time. Their main limitations were lack of contextual information for the identified hazards and greater dependency on the user's expertise and ability to tackle hazards of different nature. Tools C and D utilized more systematic approaches than tools A and B by supporting risk reduction based on the description of the risk factors. Tool D is distinctive because of 1. its comprehensive structure with respect to the steps suggested in risk management, 2. its dynamic approach to hazard identification, and 3. its use of data resulting from the risk analysis.